Elective percutaneous coronary intervention in the elderly patient. (April 2011) - Johnman, Cathy; Oldroyd, Keith G; Pell, Jill P
Elderly patients account for an increasing number and proportion of patients requiring management of coronary artery disease. Whilst medical therapy remains the cornerstone of management, percutaneous coronary intervention (PCI) has been shown to improve symptoms of angina and quality of life in elderly patients. PCI is now a routine treatment for both acute and chronic coronary artery disease. In the last decade, a series of technological and therapeutic developments have reduced in-hospital complications following PCI. The transradial approach is associated with fewer vascular complications, reduced bed utilization and reduced time to ambulation. This has facilitated the introduction and expansion of outpatient PCI, which has been shown to be safe and effective in elderly patients. This article reviews the rationale for outpatient PCI in the elderly and the evidence for its effectiveness and safety.